Analisis Terhadap Putusan 3181 K/Pdt/2018 : Sengketa Apartemen Ny. Ike Farida dengan PT Elite Prima Hutama - Amelia Nabila Pramesthi; Maximiliania Krismarmita Brahman; Nabila Sanina Fadhilah; Luthfia Putri Pramesti (Mahalini: Journal of Business Law, 2024)
This article examines the interpretation of the decision of the Supreme Court of the Republic of Indonesia with number 3181/K/Pdt/2018 which focuses on disputes that occur in the apartment sector and analyzes the extent to which the decision has fulfilled the principles of the provisions regarding disputes in the apartment sector. The case involved a dispute between the manager and the unit owner regarding ownership rights, administrative responsibilities and the provision of facilities to the buyer. In the judgment, the Supreme Court emphasized the need to protect the rights of apartment owners and affirmed the manager's obligation to meet agreed service standards. This article also explores the legal arguments of both plaintiffs and defendants and the impact of the ruling on the apartment industry and consumer protection. Taking into account the legal and social context, this article advises parties who wish to enter into an engagement to be more critical and not easily fooled by developer marketing in order to reduce the possibility of similar disputes in the future.